THE EXISTENCE OF ILMU SEJATI PEOPLE IN RELIGIOUS MODERATION - mohammad irmawan jauhari; Muh. Kholid Ismatulloh (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2022)
Believers have a long history-based existence where strengthened by religions that came to the archipelago. Perguruan Ilmu Sejati as one of the streams of believers is one of the varieties of wealth that has its own characteristics. Perguruan Ilmu Sejati has the teachings of harmony in society as an indicator of religious moderation. This article seeks to explore and provide interpretations for the typology of believers in Perguruan Ilmu Sejati in religious moderation and models of believers in Perguruan Ilmu Sejati in religious moderation. This research has a qualitative approach and the type is a case study. Data obtained by means of interviews, observation, and documentation. Data analysis was carried out since data collection with three steps namely data condensation, data display, and conclusion drawing/verification. The results of the study stated that there are three types of believers in the Perguruan Ilmu Sejati namely core members, strict members, and ordinary members. Each has a different character and also a way to apply an attitude of religious moderation. Two models of practicing Perguruan Ilmu Sejati in religious moderation are the flexibility and active role of members of the Perguruan Ilmu Sejati in society. Flexibility is built from communication Intense internal work from members of the Perguruan Ilmu Sejati at the research location. The active role of Perguruan Ilmu Sejati members in social life starts with the example of the chairman for the members. They feels called and wants to contribute positively for the common good in society.